Analisis peran perwira kapal saat kondisi darurat di perairan sempit - Muhamad Widiyantoro; Khotimatus Sholihah (Journal Marine Inside, 2025)
Insiden blackout pada MV Dali saat melintas di perairan sempit di bawah Jembatan Francis Scott Key, Baltimore, menegaskan tingginya risiko pelayaran di alur terbatas—situasi yang juga kerap ditemui pada kapal-kapal yang melayari sungai besar di Indonesia. Dalam konteks ini, kecakapan pelaut (ordinary seamanship) dan kesiapsiagaan perwira anjungan dalam menghadapi keadaan darurat menjadi prasyarat mutlak. Pelatihan berulang dan terstruktur diperlukan untuk memastikan respons yang cepat, tepat, dan terkoordinasi. Penelitian ini bertujuan merumuskan kebijakan peningkatan kompetensi pelaut dan keselamatan pelayaran di perairan sempit melalui penguatan kemampuan teknis dan prosedural awak, standarisasi latihan keadaan darurat, serta penyiapan sistem dukung operasional yang berkesinambungan. Temuan diharapkan menjadi dasar bagi penyusunan program pelatihan, pembaruan prosedur darurat, dan peningkatan tata kelola keselamatan di alur pelayaran sempit.   The blackout incident on MV Dali while transiting the confined waters beneath the Francis Scott Key Bridge in Baltimore highlights the high risks of navigation in restricted channels—conditions also frequently encountered by vessels operating on Indonesia’s major rivers. In this context, seafarers’ proficiency in ordinary seamanship and bridge officers’ readiness to handle emergencies are essential. Recurrent, structured training is required to ensure responses that are rapid, accurate, and well-coordinated. This study aims to formulate policy recommendations to enhance seafarers’ competence and navigational safety in confined waters through strengthening technical and procedural capabilities, standardizing emergency drills, and establishing continuous operational support systems. The findings are expected to inform training programs, updates to emergency procedures, and improvements in safety governance for narrow-channel navigation.